Accuracy and reliability of the Myotest Pro system to evaluate a squat jump - Houel, N.; Faury, D. D. A.; Seyfried, D. (Procedia Engineering, 2011)
During the past five years, systems with small accelerometers have been increasingly used to measure human sport motion. Few studies have defined the measurement error and limit of agreement of those systems in the particular case of squat jump when the sensor is directly fixed to the athlete. The aim of this study is to define the measurement accuracy of the centre of mass of the subject with the use of the Myotest Pro system (Myotest SA, Swiss). The reliability of the Myotest Pro system measurement is compared to those of a force platform. Nine male subjects performed squat jumps on a force platform. The data of both the tools (force platform and the Myotest Pro system) are synchronized at the instant of maximal velocity (Vmax). For each jump, data of the force platform and Myotest Pro were converted to define maximal velocity (Vmax), take off velocity (Vtoff) and the flight time (t), using the same method. Paired t-test, r correlation coefficient and Bland & Altman test were used to compare the validity and the limit of agreement between the two tools. Results showed no significant difference between the measurements of Vmax and Vtoff. Significant difference was observed between the measurements of t (p < 0.005). The correlation between the tool's measurements for Vmax, Vtoff and t is respectively r > 0.92, r > 0.58 and r > 0.77. Bland & Altman test shows very low bias and high reliability (± 0.125 m.s-1) between tools for Vmax data. Bland & Altman test shows a significant under estimation of the bias for t data of the Myotest Pro system and low reliability for Vtoff data (± 0.35 m.s-1). In conclusion, the Myotest Pro system can only be used to evaluate Vmax of subject's centre of mass during a squat jump with acceptable accuracy and reliability. Myotest Pro cannot be used to estimate other kinetic's parameters of the centre of mass of the subject during a squat jump. These results can be explained by the hypothesis of measurements between both tools (centre of mass versus side of the hip).